The interlink between capital structure, sales growth, and sustainable growth rate: Comparative insights from IDX Growth and IDX Sharia Growth - Gunawan, William Ben (UNKLAB Business School, 2025)
The dynamics of capital structure (CS), sales growth (SG), and sustainable growth rate (SGR) play pivotal roles in corporate finance, impacting a company’s valuation and strategic direction. This study investigates the factors influencing the SGR of companies listed in the IDX Growth 30 and IDX Sharia Growth indices, focusing on the roles of CS and SG. Using a quantitative approach, secondary data from the financial reports of these companies from 2022 to 2023 were analyzed through regression and comparative statistical methods. The findings reveal distinct influences on SGR for each index: within the IDX Growth 30, SG significantly impacts SGR positively, emphasizing the importance of revenue expansion and internal funding, while CS does not show a significant effect. In contrast, for IDX Sharia Growth firms, CS significantly influences SGR, highlighting the effective use of ethical financing sources, whereas SG does not. Despite these differences, there are no significant gaps in SGR between sharia-compliant and non-sharia firms, indicating that both achieve comparable sustainable growth through their respective strategies. Only CSs are different between these two types of firms. These results suggest that tailored growth strategies are essential, with conventional firms focusing on sales and market expansion and sharia-compliant firms leveraging ethical financing and operational efficiencies. Future research should consider additional variables like ownership structure and macroeconomic factors to further understand their impact on SGR across different firm categories.